Case Report: Flurbiprofen-induced Type I Kounis syndrome - Tang, Chao; Chen, Yuqi; Gu, Xiaosong (Frontiers in Cardiovascular Medicine, 2023)
Background Kounis syndrome is a specific type of acute coronary syndrome caused by allergic or hypersensitivity response. Clinical knowledge about this syndrome is insufficient. We report a case in which intravenous administration of flurbiprofen resulted in Type I Kounis syndrome. Case summary A 60-year-old female patient with no history of coronary artery disease developed limb erythema, hypotension, and chest tightness after receiving intravenous flurbiprofen. Electrocardiogram showed ST segment elevation in leads II, III, and aVF. Emergency coronary angiography revealed no significant stenosis or thrombus in the coronary arteries. Subsequent echocardiography showed no apparent abnormalities. Levels of troponin T were elevated. The diagnosis was flurbiprofen-induced Type I Kounis syndrome, presenting as acute ST segment elevation myocardial infarction. Conclusions Patients with Kounis syndrome can exhibit severe clinical symptoms, and their condition may even be life-threatening. It is important for clinicians to have a thorough understanding of this syndrome in order to develop comprehensive treatment plans.